2020
DOI: 10.1590/s1678-9946202062005
|View full text |Cite
|
Sign up to set email alerts
|

Presence of genes encoding enterotoxins in Staphylococcus aureus isolates recovered from food, food establishment surfaces and cases of foodborne diseases

Abstract: The aim of this study was to describe the microbiological characteristics and profile of genes encoding enterotoxins in 95 Staphylococcus aureus isolates obtained between April 2011 and December 2014 from foodstuffs, persons and surfaces of retail food stores. After microbiological identification and antimicrobial susceptibility testing, polymerase chain reactions (PCR) were performed, targeting sea, seb, sec, sed and see genes that code for classical enterotoxins (ET) A-E, and three additional genes: seg, seh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The 80 isolates of the present study were subjected to multiplex PCR protocol for 9 enterotoxin genes and the results revealed that 52.50% (42/80) of the isolates in the present study were enterotoxigenic harboring either one or more gene. Machado et al (2020) noted that 54.7% of the examined S. aureus isolates recovered from food, food handlers and contact surfaces from Uruguay harbored one or more of the investigated enterotoxin gene types. In similar lines, Sahin et al (2020) in Turkey and Li et al (2018) in the People's Republic of China indicated that 69% and 46% of the S. aureus isolates from raw chicken meat was positive for one or more toxin genes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 80 isolates of the present study were subjected to multiplex PCR protocol for 9 enterotoxin genes and the results revealed that 52.50% (42/80) of the isolates in the present study were enterotoxigenic harboring either one or more gene. Machado et al (2020) noted that 54.7% of the examined S. aureus isolates recovered from food, food handlers and contact surfaces from Uruguay harbored one or more of the investigated enterotoxin gene types. In similar lines, Sahin et al (2020) in Turkey and Li et al (2018) in the People's Republic of China indicated that 69% and 46% of the S. aureus isolates from raw chicken meat was positive for one or more toxin genes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The 80 isolates of the present study were subjected to multiplex PCR protocol for 9 enterotoxin genes and the results revealed that 52.50% (42/80) of the isolates in the present study were enterotoxigenic harboring either one or more gene. Machado et al. (2020) noted that 54.7% of the examined S. aureus isolates recovered from food, food handlers and contact surfaces from Uruguay harbored one or more of the investigated enterotoxin gene types.…”
Section: Resultsmentioning
confidence: 99%
“…The PCR was done with specific primers that targeted the prototypic enterotoxin B gene (Machado et al, 2020). Specific primers used for amplifying enterotoxin B gene were SEB-F (5ʹ-ACATGTAATTTTGATATTCGCACTG-3ʹ) and SEB-R (5′-TGCAGGCATCATGTCATACCA-3′), with amplicon size of 667 base pairs.…”
Section: Molecular Detection Of Enterotoxin B In Mrs Isolatesmentioning
confidence: 99%
“…Foodborne Diseases (FBD) have been considered one of the main public health problems worldwide, including in developed countries [ 5 , 6 ]. Besides that, they are important causes of morbidity and mortality and therefore an important obstacle to global socioeconomic development [ 6 , 7 ]. Investment in improving food safety management capacity may have significant economic and public health benefits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%